PENGARUH PENINGKATKAN PARTISIPASI POLITIK PEREMPUAN DI INDONESIA SETELAH MERATIFIKASI CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINTS WOMEN ( CEDAW ) - Octina, Assyura Indah; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Convention on the Elimination of All Form Discrimination Against Women (CEDAW) is a structure created to prevent discrimination. CEDAW is the most comprehensive treaty on human rights which stipulates the obligation to legally bind participating countries to discriminate against women, states the equality of civil, political, economic, socio-cultural rights between men and women, and stipulates that discrimination against women must go through steps general policies, programs and policies.This study will discuss the effect of increasing women's representation in politics after Indonesia ratified CEDAW. This study uses a constructivist perspective, analysis at the nation-state level, using Integrated Theory, the method used is qualitative with library research data collection.From this research, several things can be known. first, women's political participation existed before the ratification of CEDAW. Second, during the New Order era, women's participation declined because of the state situation at that time. Third, ratifying CEDAW has consequences where Indonesia takes affirmative action to eliminate all forms of discrimination against women by establishing a law. Keywords: CEDAW Ratification, women's political participation, Affirmative Action